WORKER REQUIREMENT ANALYSIS OF CENTER FUSELAGE PANELIZATION SYSTEM IN CN-235 AIRCRAFT PT DIRGANTARA INDONESIA - AYU KUSUMA WARDANI, LINDA
PT Dirgantara Indonesia is a state-owned company that runs an aircraft production business. CN-235 is one of type plane with high demand which is 6 units per year with takt time value of 2 months. In actual conditions, PT DI can only procudes 4 units of aircraft in a year so company must pay a penalty. The longest aircraft production stage occurs in the assembly division, especially the assembly of fuselage components. This component is divided into three large jigs namely center, rear and nose fuselage. The less optimal of operation step for barel system makes the company want to change the assembly system from a barrel system to panel system that will be applied first to the assembly of center fuselage. The panel system will break the operation with a long duration into several operations with a shorter time. This system affects the breakdown from one jig of center fuselage into 5 smaller jigs based on structural design. One of the impacts from panel system is changing needs of workers so that the optimal worker needs are required and demand of 6 units aircraft in a year is met with minimum labor costs. The assembly workers have 2 levels used, namely workers of level 2 and level 3. Each operation has workers' needs from range of 2 to 4 workers. The difference in the number and level of workers used affects the time of each operation and the cost of workers. A mathematical model with multi-manned assembly line balancing problem (MMALBP) and type of mixed integer linear programming (MILP) is developed to meet the actual conditions. The computation process for each jig (work station) is 4 times in accordance with the specified worker needs. Each jig has more than one solution so comparisons are designed between computational results. The results of the comparison gives one of the best solutions, as many as 7 workers of level 3 and 3 workers of level 2 with labor cost of Rp38.855.000 per month or Rp466.260.000 per year and the longest assembly time of 278.6 hours (1.9 months).